Literasi Review: Urgensi Pendidikan Seks di Sekolah: Mencegah Bukan Mengajarkan - Nadia Nadila; Ayu Nafira; Cut Kumala Sari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Sex education is still taboo in society. Thus, it results in the implementation of sex education in schools not being optimal. The factor that influences the less than optimal implementation of sex education in schools is that many parents still have the wrong perception regarding sex education. Thus, through this study aims to review scientific articles in order to collect relevant sources related to the urgency of implementing sex education in schools. The method used in writing this article is a literature review. The study began by looking for articles related to the research topic to be carried out. The criteria for scientific articles used as data are in the form of scientific articles sourced from national and international journals with the latest 10 years, namely from 2015-2025. The results of the analysis of 12 journal articles obtained more developed types of literature review research and descriptive qualitative than other types of research. The results of the analysis show that sex education plays a major role in increasing self-awareness, maintaining the body, and forming good moral, social, and spiritual characters in children and adolescents. This education not only discusses the human body, but also teaches ethical values, responsibility, and how to control oneself, which need to be conveyed by paying attention to moral and religious values.